(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In The Mistress of Spices, named a standout amongst other books of the twentieth Century by the San Francisco Chronicle, the courageous woman Tilo gives spices, for cooking, as well as for the yearning to go home and estrangement that the Indian immigrants she would say. In Sister of My Heart, two cousin’s one in America, the other in India, share points of interest of their lives with each other and help each other tackle issues that undermine their marriages. In One Amazing Thing, a gathering of outsiders of fluctuated foundations, caught by a seismic tremor in an Indian visa office, find what they have in like manner as they battle to spare themselves. Divakaruni writes to join individuals. Her points are to pulverize fantasies and generalizations. She trusts through her written work to break up limits between individuals of various foundations, networks and ages.